Assessment of Midwives' Communication Skills at the Maternity Wards of Teaching Hospitals in Mashhad in 2014 - Talate Khadivzadeh; Maryam Sadat Katebi; Zohre Sepehri Shamloo; Habibolah Esmaily (Mashhad University of Medical Sciences, 2015)
Background & aim:The quality of communication between midwives and parturient women is a determinant of maternal satisfaction with midwifery care. Therefore, this study was conducted to determine the communication skills of midwives at maternity wards of Mashhad teaching hospitals in 2014.   Methods:In this descriptive study, 49 midwives, working at Mashhad teaching hospitals, were randomly selected. All midwives worked rotating shifts at the wards. The midwives' communication skills were assessed by the researcher, using the self-structured  observation checklist of communicative performance.   Results: The mean age of midwives was 39.11±9.66 years and their mean work experience was 15.9±8.77 years. In total, 68.3% of the participants experienced childbirth themselves. 66.7% of midwives were moderately  keen on midwifery as a profession. The mean score of the checklist obtained by midwives was 67.9±10.7. There was no relationship between midwives' communication skills and work experience, childbirth experience, age or interest in midwifery. Conclusion:Considering the inadequacy of midwives' communication skills, which could be the major cause of maternal dissatisfaction with delivery care, it is recommended that in-service training courses be held by applying new teaching methods. Moreover, the educational needs of midwives, including communication skills, should be considered in these training programs .